Draft Outline Fifth Five Year Plan Assam Volume II (Sectoral Programmes) - Planning Commission (Planning Commission, 1973)
During the first three years of the Fourth Plan, a sum of Rs.523.84 lakhs was spent for Agricultural Programmes for the General Areas of the State. An expenditure of Rs.213.22 lakhs (provisional) was incurred during 1972-73. The outlay for 1973-74 is Rs. 216.00 lakhs. It is, there fore, expected that about Rs. 953.06 lakhs would be spent by the end of 1973-74 as against the Fourth Plan allocation of Rs. 960.09 lakhs.
Government of Assam, Planning and Development Department